A case study of the Omani Ministry of Health’s approaches to nursing education and its cultural congruency - Al Junaibi, Suad Moosa Noor (2016)
Culture is a complex concept, but it is central to the task of curriculum design and development. The Ministry of Health (MoH) in the Sultanate of Oman plays a major role in healthcare education because it is the main employer and producer of healthcare professionals in the country. The MoH claims that its educational programmes are designed to meet the healthcare needs of the country at international standards, with ample consideration to the culture. As nursing is the major profession that the MoH invests in, produces, and employs, the purpose of this study is to explore the MoH’s approaches to designing, developing, and implementing the current basic (general) nursing curricula and its cultural congruency in the context of Oman. A qualitative case study design is used to answer the research questions. Educational policy documents, semi-structured qualitative individual interviews and focus groups have been used to collect data from the MoH’s nursing education decision makers, educators, students and service users (public) over a period of six months. Data was analysed using RichieRitchie and Spencer’s five-stage analytical framework to identify the themes from the data collected from the documents and the interviews. A purposeful sampling was used to select study participants from the MoH nursing education decision makers, educators, students and service users. Findings of the study reveal that the MoH’s current approach to nursing curriculum fails short of what Denis Lawton considers a culturally competent curriculum. The study proposes a framework, adapted from Lawton’s cultural analysis model, aimed at developing culturally congruent nursing education in Oman.